Formação De Agenda Conservadora No Congresso Nacional: O Caso Da Redução Da Maioridade Penal (Pec 171/1993) - Lino, Lillian Lages [UNIFESP] (2017)
This dissertation aims to analyze and comprehend the agenda-setting process, in the legally punishable age case. Received for the first time in 1993, despite of Executive’s opposition , the PAC 171 that aims to reduce the legally punishable age to 16 years old was approved in the Chamber of Deputies in 2015 and now it is in Senate. Applying the Multiple Streams Model, by John Kingdon, this research aspires to discuss which are the factors that mobilizes agenda-setting and the strength correlation established in today's parliamentary term in Chamber of Deputies. Willing to explain the result of the voting process in the Chamber of Deputies and analysing the procedure of PEC 171, it will be exposed the main arguments used by the agenda-setters, interests of different groups, party’s political leadership orientation, the parliamentary fronts behavior, the roles performed by the Federal Government (against the project) and by the Chamber of Deputies' leader (in favor). With these elements, the purpose is to verify the reasons that, in a scenario of conservadorism advance, made possible to open the policy window.